Influence of acidic monomer concentration and application mode on the bond strength of experimental adhesives - Cibele Cândida de Almeida KINTOPP; Adilson Yoshio FURUSE; Reginaldo Mendonça COSTA; Fernanda Sandes de LUCENA; Gisele Maria CORRER; Carla Castiglia GONZAGA
Abstract The aim of this research was to evaluate the influence of MDP (10-methacryloyloxydecyl dihydrogen phosphate) concentration and application mode of experimental adhesives on microshear bond strength (μSBS) to dentin after storage in distilled water at 37°C for 24h and 6 months. Five experimental adhesives were prepared with: CQ, DABE, BHT, ethanol, HEMA, TEGDMA, Bis-EMA, UDMA, and Bis-GMA. Concentrations of 0 wt%, 3 wt%, 9 wt%, 12 wt% or 15 wt% of MDP were added to their composition. The adhesives were applied to flat dentin surfaces in etch-and-rinse or self-etching modes. Cylindrical molds filled with light-cured composite resin were placed above the dentin. The specimens were stored in distilled water at 37oC for 24h or 6 months and submitted to μSBS testing. The adhesives were also submitted to pH analysis. The data were analyzed by one-way ANOVA, three-way ANOVA and Tukey's test (α = 5%). All the adhesives used in the etch-and-rinse mode showed significantly higher bond strength than the adhesives applied in the self-etching approach. The 9 wt% adhesive showed the highest bond strength values, and 3 wt% was most stable after storage. A strong negative correlation between MDP concentration and pH was observed. It was concluded that the formulations with low concentrations of MDP (up to 9 wt%) showed better results for bond strength and bond strength degradation over time.